1998
DOI: 10.1089/vim.1998.11.93
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutation of a Rubella Virus E1 Protein T-Cell Epitope by Substitution of Single Amino Acid Reversed the Restrictive HLA-DR Polymorphism: A Possible Mechanism Maintaining HLA Polymorphism

Abstract: The influence of single amino acid substitutions within a rubella E1 protein T-cell epitope, E1(273-284) on T-cell recognition was studied. Substitutions of an uncharged amino acid A for an E or for a T and substitution of a T for S were found to not significantly reduce the T-cell responses. However, substitution of a charged residue such as E for hydrophobic residues (I, V, or W); D for Q; or a relatively larger size amino acid for polar residues completely abolished the cytotoxicities mediated by E1(273-284… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The humoral antibody responses are predominantly directed against rubella virus E1 and E2 glycoproteins [9,10]. Additionally, rubella E1 protein has been demonstrated to be the most important rubella virus antigen to which the majority of the human population develops a lymphocyte proliferative response [11].…”
Section: Introductionmentioning
confidence: 99%
“…The humoral antibody responses are predominantly directed against rubella virus E1 and E2 glycoproteins [9,10]. Additionally, rubella E1 protein has been demonstrated to be the most important rubella virus antigen to which the majority of the human population develops a lymphocyte proliferative response [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also reported that the mutations in T cell epitope and glycosylation sites could eliminate the neutralizing capacity in a different type of virus [23][24] to suggest a potential effect on the ability of antibodies induced by the MUV vaccine strain to neutralize wild-type viral strains.…”
Section: Discussionmentioning
confidence: 98%
“…This conservation extends to the breeds studied here, and is particularly evident in aminoacids at positions 70, 71, and 74 of pocket 4, which occupies a central position within the peptide binding groove. These aminoacids have been implicated as playing a signi cant role in human immune responsiveness (58), but also correlated with vaccine responses and infectious disease susceptibility or tolerance in bovines (55,(59)(60)(61). In this sense, it could be hypothesized that eventhough bovine breeding programs make use of extensive crossing, there may be a functional constraint in the PBR to BoLA-DRB3 aminoacid variability.…”
Section: Discussionmentioning
confidence: 99%